THE CHANGING CLINICAL PERFORMANCE OF DENGUE VIRUS INFECTION IN THE YEAR 2009 - Soegijanto, Soegeng; Susilowati, Helen; Mulyanto, Kris Cahyo; Hendrianto, Eryk; Yamanaka, Atushi (Institute of Topical Disease Universitas Airlangga, 2012)
Background: Dengue (DEN) virus, the most important arthropod-borne human pathogen, represents a serious public health threat. DEN virus is transmitted to humans by the bite of the domestic mosquito, Aedes aegypti, and circulates in nature as four distinct serological types DEN-1 to 4). The aim of Study: To identify Dengue Virus Serotype I which showed mild clinical performance in fiveyears before and afterward showed severe clinical performance. Material and Method: Prospective and analytic observational study had been done in Dr. Soetomo Hospital and the ethical clearance was conduct on January 01, 2009. The population of this research is all cases of dengue virus infection. Diagnosis were done based on WHO 1997. All of these cases were examined for IgM & IgG anti Dengue Virus and then were followed by PCR examination to identify Dengue Virus serotype. Result and Discussion: DEN 2 was predominant virus serotype with produced a spectrum clinical illness from asymptomatic, mild illness to classic dengue fever (DF) to the most severe form of illness (DHF). But DEN 1 usually showed mild illness. Helen at al (2009–2010) epidemiologic study of Dengue Virus Infection in Health Centre Surabaya and Mother and Child Health Soerya Sidoarjo found many cases of Dengue Hemorrhagic Feverwere caused by DEN 1 Genotype IV. Amor (2009) study in Dr. Soetomo Hospital found DEN 1 showed severe clinical performance of primary Dengue Virus Infection as Dengue Shock Syndrome two cases and one unusual case.Conclusion: The epidemiologic study of Dengue Virus Infection in Surabaya and Sidoarjo; in the year 2009 found changing predominant Dengue Virus Serotype from Dengue Virus II to Dengue Virus 1 Genotype IV which showed a severe clinical performance coincident with primary infection.